Stereotyping as a barrier to the social participation of older adults with low vision: a qualitative focus group study. Issue 9 (3rd September 2019) - Fraser, Sarah; Beeman, Irene; Southall, Kenneth; Wittich, Walter
Abstract : Objective: In order to better understand the barriers that limit the social participation of older people with low vision, the aim of this study was to describe and clarify the factors that shape the social participation of older adults with vision loss. Methods: As part of a study on rehabilitation access barriers, six qualitative focus groups were conducted in a private room in a hospital, with 21 individuals with low vision (aged 38–92 years) who had or had not accessed low vision services. During the focus groups, participants often spoke of the challenges they faced when interacting with people with 'normal' vision; this discussion led to a modification of the interview guide in order to capture barriers to social participation. Focus group discussions were audiotaped and transcribed, and content analysis was conducted. Results: Content analysis revealed that personal as well as environmental factors influenced the social participation of older adults with low vision. Four themes emerged: 1) experiencing the onset of impairment and degenerating ability, 2) the physical environment, 3) attitudes and responses from others and 4) individual internal attitude and responses during social interactions. Lived and perceived stigma from the perspective of the insider (person living with low vision) interacting with an outsider (person with 'normal' vision) and difficult environmental contexts were described as barriers to social participation and optimal functioning. Conclusion: At a personal level, transitioning from an outsider to an insider influenced self-identity and social participation. Further, insiders experiencing stereotypes associated with older adults who are blind had a negative impact on their social participation. Findings highlight the importance of stigma and stereotyping in the lived experience of older adults with low vision. Stigma is persistent, but strategies to reduce stigma will ultimately facilitate the social participation of older adults with low vision.